2008
DOI: 10.1063/1.2832672
|View full text |Cite
|
Sign up to set email alerts
|

The influence of metallic particle size on the mechanical properties of polytetraflouroethylene-Al–W powder composites

Abstract: The dynamic mechanical properties of reactive materials (e.g., high density mixtures of polytetraflouroethylene (PTFE), aluminum (Al) and tungsten (W) powders) can be tailored by changing the morphology of the particles and porosity. Cold isostatically pressed PTFE-Al-W powder composites with fine metallic particles and a higher porosity exhibited higher ultimate compressive strength than less porous composites having equivalent mass ratios with coarse W particles. The mesoscale force chains between the fine m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…This behavior is similar to observations in the PTFE-Al-W mixtures and in the experiments with the Al-W powder mixture. 11,12,[16][17][18] The global shear localized zones and the subsequent cracks developed at an approximate 45 degree angle but was kinked by the rigid W particles resulting in the initial shear band forming in a range of angles from 36 to 50 degrees (see Fig. 9).…”
Section: Numerical Modeling and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior is similar to observations in the PTFE-Al-W mixtures and in the experiments with the Al-W powder mixture. 11,12,[16][17][18] The global shear localized zones and the subsequent cracks developed at an approximate 45 degree angle but was kinked by the rigid W particles resulting in the initial shear band forming in a range of angles from 36 to 50 degrees (see Fig. 9).…”
Section: Numerical Modeling and Discussionmentioning
confidence: 99%
“…Multimaterial Eulerian hydrocode simulations of the dynamic tests for the various types of samples were used to elucidate the observed experimental results. 11,16,18 The complexity of the dynamic behavior of granular/porous materials is caused by the significant role of the mesoscale parameters including the particle sizes of components, the formation of force chains, the morphology of particles, and the bonding between particles. In these materials, shear localization and fracture can be delayed by strain hardening mechanisms such as compaction which results in porosity reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that particle size [15,19,21,22], shape [23] and concentration [24] and properties of the constituents can affect mechanical properties. In Al 2 O 3 particle-filled epoxy (Epon 828/Z), increasing the particle concentration and decreasing the particle size is found to increase the stress corresponding to 4% plastic strain [25].…”
mentioning
confidence: 99%
“…Increasing volume fraction of particulates in the composite resulted in decreased strength. particle size, loading fractions, particle type and the adhesion between the particulate and the matrix [15,[17][18][19][20].…”
mentioning
confidence: 99%